PENGARUH PARAMETER PROSES TERHADAP KEKUATAN TARIK FILAMEN ST-PLA MENGGUNAKAN METODE TAGUCHI - Yulian Subakti M.yusuf; Hasdiansah Hasdiansah (Politeknik Manufaktur Negeri Bangka Belitung, 2021)
Fused Deposition Modeling (FDM) is a popular 3D Printing technique used to print the desired product. The printed product certainly has the ideal tensile strength characteristics if it has a precise size and perfect shape. One of the materials that can be processed in a 3D printing machine is ST PLA. Research in terms of tensile testing has been carried out on PLA and ABS materials. Meanwhile, tensile testing with using ST PLA filaments is still rarely done.. The research was conducted using a 3D printer DIY machine with a Prusa model with a printing area of ​​XYZ, 300 mm X 300 mm X 300 mm. The material used was a ST PLA filament diameter of 1.75. For the process parameters in this study are Layer Thickness, Nozzle Temperature and Flowrate. The shape of the test specimens followed ASTM D638 Type IV standards. As for the design of process parameters using the Taguchi L9 method (33). Process parameter values ​​that produce the highest tensile strength without annealing are Layer thickness 0.3 mm, nozzle temperature 205 0C, and flowrate 100%.